2023
DOI: 10.1002/adsc.202201103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Acyl Fluorides from Carboxylic Acids with KI/AgSCF3 for Efficient Amide and Peptide Synthesis

Abstract: A facile synthesis of acyl fluorides from carboxylic acids in a practical and byproduct-free manner was effected with commercially available KI/AgSCF 3 reagents under conditions of high functional group tolerance, and the acyl fluoride intermediates were easily transformed to the corresponding esters, amides, and several carbon-carbon bondforming products. This approach can be successfully applied to straightforward peptide synthesis from amino acids including sterically hindered amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The formation of amide bonds from the reaction of acyl halides and amines is one of the most atom-efficient pathways and therefore produces minimal waste in relation to the method mediated by activators. Although acyl chlorides are the most common acyl halides for amidation reactions, the use of acyl fluorides has recently attracted attention because of their stability and facile operation. The reaction between acyl fluorides and amines is typically performed in the presence of a base in a solvent. During the optimization of the conditions for the reaction of acyl fluoride 2a and n -butyl amine ( 3a ) to afford amide 4aa , we observed that mechanochemical coupling proceeded smoothly to afford 4aa in 93% yield without any base or solvent (Scheme B). This outcome was similar to that obtained in the presence of Et 3 N (2.0 equiv), yielding 4aa in a 94% yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The formation of amide bonds from the reaction of acyl halides and amines is one of the most atom-efficient pathways and therefore produces minimal waste in relation to the method mediated by activators. Although acyl chlorides are the most common acyl halides for amidation reactions, the use of acyl fluorides has recently attracted attention because of their stability and facile operation. The reaction between acyl fluorides and amines is typically performed in the presence of a base in a solvent. During the optimization of the conditions for the reaction of acyl fluoride 2a and n -butyl amine ( 3a ) to afford amide 4aa , we observed that mechanochemical coupling proceeded smoothly to afford 4aa in 93% yield without any base or solvent (Scheme B). This outcome was similar to that obtained in the presence of Et 3 N (2.0 equiv), yielding 4aa in a 94% yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Subsequently, we assessed the generality of the process in terms of alkyl carboxylic acids. Primary (13), secondary (14), and tertiary ( 15) carboxylic compounds all yielded the corresponding acyl fluorides in good-to-excellent yields (78-95% yields). Similar success was observed when an α,β-unsaturated carboxylic acid was used (16, 81% yield).…”
mentioning
confidence: 98%
“…[12] Acyl fluorides are isolable and exhibit increased stability with respect to other acyl halides, and yet require mild reaction conditions to engage in diverse synthetic transformations. [13] Thus, when reacted with nucleophiles, they offer a straightforward route to a wide range of valuable products such as esters, amides, or thioesters, almost regardless of the steric and electronic properties. [14] Herein, we report the development of a strategy that harnesses the power of a microfluidic device to form thionyl fluoride and swiftly use it to convert carboxylic acids into acyl fluorides (Scheme 1C).…”
mentioning
confidence: 99%
“…12 Acyl fluorides are isolable and exhibit increased stability with respect to other acyl halides and yet require mild reaction conditions to engage in diverse synthetic transformations. 13 Thus, when reacted with nucleophiles, they offer a straightforward route to a wide range of valuable products such as esters, amides, or thioesters, almost regardless of the steric and electronic properties. 14 Herein, we report the development of a strategy that harnesses the power of a microfluidic device to form thionyl fluoride and swiftly use it to convert carboxylic acids into acyl fluorides (Scheme 1C).…”
mentioning
confidence: 99%